2018
DOI: 10.29252/.22.6.408
|View full text |Cite
|
Sign up to set email alerts
|

Novel LAMA2 Gene Mutations Associated with Merosin-Deficient Congenital Muscular Dystrophy

Abstract: Background:Merosin-deficient congenital muscular dystrophy (MDC1A) is a rare autosomal recessive genetic disease occurred due to mutations in the LAMA2 gene. This study investigated the molecular genetics of three Iranian MDC1A patients who manifested hypotonia, muscle weakness at birth, elevated levels of creatine kinase, and normal magnetic resonance imaging before the age of six months.Methods:Peripheral blood samples were collected from three unrelated patients and their families after obtaining informed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…In previous studies, patients with LAMA2 mutations, showed normal brain magnetic resonance imaging (MRI) when has been detected during the neonatal period or in the first 6 months of life [ 11 13 ]. However, white matter abnormalities have been shown in the later period of life except for the case of an Italian patient reported by Saredi et al [ 14 ], who carried a compound heterozygous nonsense mutation with an atypical phenotype and nearly normal brain MRI performed at 16 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, patients with LAMA2 mutations, showed normal brain magnetic resonance imaging (MRI) when has been detected during the neonatal period or in the first 6 months of life [ 11 13 ]. However, white matter abnormalities have been shown in the later period of life except for the case of an Italian patient reported by Saredi et al [ 14 ], who carried a compound heterozygous nonsense mutation with an atypical phenotype and nearly normal brain MRI performed at 16 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Merosin was absent in all patients. Hashemi-Gorji et al [ 47 ] identified a likely pathogenic missense variant, c.8665G>A (p.G2889R), in two unrelated Iranian boys of consanguineous parents. Both patients presented with a hypotonia since birth and elevated CK and aldolase in the first year of life.…”
Section: Discussionmentioning
confidence: 99%
“…One patient had kyphosis and contractures of elbow and wrist at age 7 years. Another patient also had kyphosis and normal cognitive function at age 6 years [ 47 ]. Recently, two homozygous variants, c.2882G>A (p.A961T) and c.4406G>A (p.C1469Y), were reported in a Chinese patient who presented with seizures, slight weakness of the proximal leg muscles, mild cognitive impairment, and severe leukoencephalopathy [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…ANK2 variant is mainly related to arrhythmia phenotypes [45]. LAMA2 is linked with muscular dystrophy [46]. SRRM2 is associated with Parkinson's disease and papillary thyroid carcinoma [47,48].…”
Section: Comparative Analysismentioning
confidence: 99%